2015
DOI: 10.1111/1759-7714.12158
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary cancers involving lung cancer at a single tertiary hospital: Clinical features and prognosis

Abstract: BackgroundThe development of other primary cancers in patients with lung cancer is unfortunate and uncommon, although the frequency is increasing. The aim of this study was to determine the clinical features and prognosis in patients with multiple primary cancers (MPC) involving lung cancer.MethodsAfter a retrospective review of 1644 patients who were newly diagnosed with primary lung cancer between 1998 and August 2012 at a tertiary hospital, 105 patients were included.ResultsThe median age at the time of lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
(29 reference statements)
1
13
0
Order By: Relevance
“…The later the stage of lung cancer, the worse the prognosis. This was also in line with the findings of other studies (11,12). Massard et al (11) reported that the survival of LCSPM patients was associated with the stage of lung cancer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The later the stage of lung cancer, the worse the prognosis. This was also in line with the findings of other studies (11,12). Massard et al (11) reported that the survival of LCSPM patients was associated with the stage of lung cancer.…”
Section: Discussionsupporting
confidence: 91%
“…It should be noted that lung cancer here referred only to NSCLC, and the prognosis of dual primary cancer patients with SCLC as a second primary malignancy had no relation to the FPC. Kim et al (12) observed that cancer patients with another primary malignancy in the head and neck tended to have a worse prognosis than these patients with another primary malignancy elsewhere. Unfortunately, due to so few cases (less than 1.3%) with FPC in the head and neck, our study did not separately compare the prognosis of these patients with those of other patients, which may result in different results.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in pulmonary and cardiovascular functions, impaired wound healing, diminished immune response, increased risk of infections and bleeding episodes, delaying in administration of neoadjuvant therapy, increased recurrence, second primaries, and high mortality are all associated with smoking and alcohol consumption. [22][23][24][25] These changes can be reversed to some extent by discontinuation in pre-operative period. Counseling with administration of continuous nicotine replacement therapy and Vareniciline either alone or in combination may be helpful in cessation.…”
Section: Role Of Smoking and Alcohol Cessation In Surgical Prehabilitmentioning
confidence: 99%
“…MPMs are further divided into synchronous and metachronous malignancies. The synchronous group is defined as the diagnosis of a second malignancy within six months of initial primary, and the metachronous group is defined as diagnosis after six months of initial primary [2]. It is important for the clinician to distinguish between MPMs and metastatic spread, as this has impacts on both prognosis and subsequent treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al showed that advanced lung cancer was an independent poor prognostic factor in both synchronous and metachronous groups. In the metachronous group, head and neck cancer as an MPM was a poor prognostic factor [2]. Other studies have demonstrated smoking as a risk factor for MPMs.…”
Section: Introductionmentioning
confidence: 99%